Renewable energy development in Africa (CSC LondonGB, 1985)
Contains papers on four broad scientific subject areas namely energy resource assessment, energy conversion technologies, energy utilization technologies, and energy policy formulation and planning. Each paper is preceded by a brief abstract. Reports the results of research projects on renewable energy technologies in Africa. Volume two contains papers on solar crop dryers, solar heat, wind power generators and biomass conversion.
Includes bibliographies